TANTANGAN DAN HARAPAN GURU ABK DI SKHN 01 SERANG DI DUNIA PENDIDIKAN ANAK TUNAGRAHITA - Yahdinil Firda Nadhirah; Siti Kholidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education plays a central role in shaping an inclusive and equitable future, particularly for children with special needs such as those with intellectual disabilities (commonly referred to as "tunagrahita" in Indonesia). These children face unique challenges in learning due to limitations in intellectual and adaptive functioning. This study employs a qualitative method with data collected through interviews and observations at SKHN 01 Serang, a special needs school. Findings indicate that tunagrahita students require tailored educational approaches, including modified curricula and support from specialized educators. Challenges include learning difficulties, limited access to facilities, and social stigma. Nevertheless, with support from the community, trained educators, and inclusive policies, these children have the potential to grow into independent and valued individuals. This study highlights the urgency of developing a more inclusive education system and social environment that ensures equal opportunities for all children.